Association of 18F-fluorodeoxyglucose uptake with cardiac events in cardiac sarcoidosis during outpatient follow-up after immunosuppression - Hideki Kawai; Masayoshi Sarai; Yasuchika Kato; Hiroyuki Naruse; Hiroshi Takahashi; Masakazu Tsujimoto; Kenta Nogami; Hiroshi Toyama; Shin-ichiro Morimoto; Hideo Izawa (PLoS ONE, 2026)
Background 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) is a pivotal tool for diagnosing cardiac sarcoidosis, but its prognostic value during the phase of stable medical and device therapy after initiation of immunosuppressive therapy remains unclear. We aimed to evaluate the prognostic significance of cardiac FDG uptake in patients with cardiac sarcoidosis after treatment initiation. Methods We retrospectively analyzed 79 patients who underwent FDG-PET/CT ≥ 12 months after initiating immunosuppressive therapy (June 2013–October 2023). Patients were categorized into the cardiac accumulation (+) and (-), and Cardiac metabolic activity (CMA) was also quantitatively measured. Major adverse cardiac events—including cardiac death, ventricular arrhythmias, ICD therapy, and heart failure hospitalization—were evaluated. Results Patients in the cardiac accumulation (+) had a higher 2-year incidence of major adverse cardiac events than those in the cardiac accumulation (-), as determined by Kaplan–Meier analysis (log-rank P = 0.030), but FDG uptake was not identified as a predictor in Cox regression analysis. In long-term outcomes, the incidence of cardiac events tended to be higher in the cardiac accumulation (+) group, although this difference did not reach statistical significance (log-rank P = 0.078). Among patients with preserved left ventricular ejection fraction (LVEF ≥50%, independently associated with fewer events), annual cardiac event rates were similarly low regardless of uptake status (1.3% vs. 0.8%; log-rank P = 0.91). In 41 patients who underwent repeat PET imaging, CMA significantly decreased (median 4.83 to 0.82, P = 0.038). Among 23 patients without intensified immunosuppression despite uptake, it resolved spontaneously in 8 patients. Conclusions Follow-up cardiac FDG uptake may be associated with an increased risk of short-term events but has limited value for predicting long-term prognosis. LVEF and the temporal dynamics of FDG uptake should be considered when managing cardiac sarcoidosis.